2003
DOI: 10.1002/elps.200305667
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA fragmentation in a single apoptotic cardiomyocyte by electrophoresis on a microfluidic device

Abstract: The detection of doxorubicin-induced apoptosis in individual cardiomyocytes was performed on a microfluidic device. Microstructures integrated on a CD-like plastic disk were adapted for the selection of individual cells their lysis in an alkaline environment and the separation of released apoptotic DNA fragments. The fragments with typical 180 base pairs ladder pattern were electrophoretically resolved in a 2% solution of linear polyacrylamide with 0.1 M NaOH on a migration distance of 6 mm. The laser-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 42 publications
0
53
0
Order By: Relevance
“…This volume compares favorably with the nanoliter volumes reported for derivatization reactions in capillary-based chemical cytometry methods (1)(2)(3)(4)(5), although smaller volumes have been reported (26). The capacity to confine a lysing, reacting plug of cell and reagents is an advantage that motivated prior work by us (8) and others (18) to use valves formed by multilayer soft lithography to confine approximately nanoliter volumes.…”
Section: Integrated Microfluidic Chip For Manipulation and Analysis Omentioning
confidence: 63%
“…This volume compares favorably with the nanoliter volumes reported for derivatization reactions in capillary-based chemical cytometry methods (1)(2)(3)(4)(5), although smaller volumes have been reported (26). The capacity to confine a lysing, reacting plug of cell and reagents is an advantage that motivated prior work by us (8) and others (18) to use valves formed by multilayer soft lithography to confine approximately nanoliter volumes.…”
Section: Integrated Microfluidic Chip For Manipulation and Analysis Omentioning
confidence: 63%
“…As the genotype within pure cell lines is usually identical, it can be argued that single-cell DNA extractions do not provide more information than regular bulk extractions. The work from Kleparnik, however, demonstrated that meaningful information can be gained from such microfluidic devices (Kleparnik & Horky 2003). They used a microfluidic device based on a commercial polycarbonate platform to semi-quantitatively measure DNA fragmentation in mouse cardiomyocytes upon doxorubicin treatment.…”
Section: Dnamentioning
confidence: 99%
“…Traditional gel electrophoresis method is labor-intensive, requiring an additional time for cell lysing, and extraction of genomic DNA. Kleparnik and Horky [32] performed the detection of doxorubicin-induced apoptosis in individual cardiomyocytes on a microfluidic device. Microstructures integrated on a CD-like plastic disk were adapted for the selection of individual cells, the lysis of cells in an alkaline environment, and the separation of released apoptotic DNA fragments.…”
Section: Dna Fragmentationmentioning
confidence: 99%